Determinação da resistência mecânica e da permeabilidade de concreto permeável: comparação entre concretos usinado e moldado em laboratório - Santos, Jonathan Rehbein dos (2020)
Faced with the soil sealing caused by urbanization and the inefficiency of drainage systems, heavy or lasting rainfall causes disruption to the population, as precipitated water generates runoff that forms floods. To solve this problem, the use of permeable pavements is being analyzed in research centers. It is a pavement projected to allow water to drain through its structure until it reaches its destination, either to a storage system or directly to the ground for infiltration to occur. The coating layer of permeable paviment can be made of different materials, including permeable concrete. This work studies the behavior of permeable concrete when produced with two types of Portland cement, CP II Z and CP V, and when used RAP (reclaimed asphalt pavement) as a substitute for part of the natural aggregates in its composition. Also, the differences imposed by the production of the material in concrete plants or in the laboratory are investigated. It is also an objective of this research to verify the difference in permeable concrete parameters between the densification and curing performed in the field and the performed in the laboratory. In addition, it was determined the representativeness that permeability tests performed in laboratory-produced permeable concrete samples have when compared to the hydraulic conductivity presented in the field, in a parking lot, through hydraulic tests. The specimens were subjected to specific mass, voids index, communicating voids, axial compression strength, diametral tensile strength, flexural tensile strength, elasticity modulus, impact and abrasion degradation resistance, conductivity tests with constant and variable load permeameters, as well as the determination of permeability in the field. Finally, with the results found, it was inspected whether the properties of the sample groups studied are in accordance with NBR 16416/2015 which addresses the specifications required for permeable pavements in the country. From the analysis of the results it was possible to observe that the machined mixture has lower voids index, increasing the mechanical resistance, but decreasing the permeability of the permeable concrete. It was concluded that the densification and curing methods employed in the laboratory are not representative with the one performed in the field, because the samples molded and cured according to laboratory methods presented superior axial compressive strength to the samples extracted from the parking lot. Specimens with CP V were more permeable but less resistant compared to CP II Z. Placing milling in the mix increased permeability, but reduced permeability of the permeable concrete. The constant load permeability test showed results closer to those found in the field than the variable load permeate test. As for the requirements imposed by the standard, all sample groups analyzed exceeded the minimum specific mass and flexural tensile strength. The permeability results found for concrete from the plant did not reach the value prescribed by the norms, either in the laboratory, through the variable and constant load permeameters, nor in the field, in the parking lot, through a specific method.